Angioni, L. (2014) (ed.). Lógica e Ciência em Aristóteles. Campinas, Ed. Phi. - Berrón, Manuel (Revista Archai, 2017)
BERRÓN, Manuel (2017). Reseña: Angioni, Lucas (2014) (ed.). Lógica e Ciência em Aristóteles. Campinas, Ed. Phi.